Who is organised civil society accountable to? - Novak, Meta (Teorija in praksa, 2017)
Organised civil society represents a linkage between government and the public. For this reason, it represents an important opportunity structure for citizens to communicate their message to the government and an important component of a functioning democracy. With no clear definition of organised civil society in the public institutions in Slovenia, it is questionable whose interests are represented by civil society organisations (CSOs) and who CSOs are accountable to. The aim of this article is two-fold: (1) to evaluate the population size of CSOs, taking into account all legal forms under which CSOs can get registered; and (2) to evaluate who CSOs are accountable to.
Keywords: Civil society; Civilna družba; Odgovornost; Political representation; Politično predstavništvo; Population; Prebivalstvo; Responsibility; Slovenia; Slovenija